Predictors and long-term outcomes of heart block after transcatheter device closure of perimembranous ventricular septal defect - Jiang, Diandong; Zhang, Simiao; Zhang, Yuxin; Lv, Jianli; Yi, Yingchun; Wang, Jing; Wang, Yan; Yang, Xiaofei; Zhang, Jianjun; Han, Bo (Frontiers in Cardiovascular Medicine, 2022)
Background Heart block is the most common and concerning complication associated with transcatheter device closure of perimembranous ventricular septal defect (pmVSD) and its occurrence remains a great challenge for device closure. Methods Between June 2002 and June 2020, 1076 pediatric patients with pmVSD, who successfully underwent transcatheter device closure in our center, were enrolled in this cohort study, with a median follow-up of 64 months (range: 1 to 19 years). Results Of 1076 patients, 234 (21.8%) developed postprocedural heart block, with right bundle branch block being the most common (74.8%), followed by left bundle branch block (16.2%), and atrioventricular block (5.6%). Complete atrioventricular block occurred in 5 cases, including 3 cases with permanent pacemaker implantation, 1 case with recovery to normal sinus rhythm, and 1 case with sudden cardiac death. Most patients (97.9%) developed heart block within 1 week of procedure. Finally, 138 cases returned to normal cardiac conduction. Multivariate logistic regression revealed that thin-waist occluders (odds ratio [OR]: 1.759; 95% confidence interval [CI]: 1.023 to 3.022; P = 0.041), and oversized devices (OR: 1.809; 95% CI: 1.322 to 2.476; P < 0.001) were independently associated with occurrence of postprocedural heart block. Moreover, heart block was less likely to occur when the left disk of occluder was placed within the aneurysmal tissue (OR: 0.568; 95% CI: 0.348 to 0.928; P = 0.024). Conclusion The outcome of postprocedural heart block is favorable in most cases. Oversized devices and thin-waist occluders should be avoided. Placement of the left disk of the device should into the aneurysmal tissue is highly recommended.